2016
DOI: 10.1007/s00380-016-0864-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antithrombotic abilities of non-vitamin K antagonist oral anticoagulants using the Total Thrombus-formation Analysis System®

Abstract: The Total Thrombus-formation Analysis System (T-TAS) is a novel automated microchip flow-chamber system for the quantitative evaluation of thrombus formation under blood flow conditions. T-TAS uses two types of microchip to evaluate thrombus formation: the AR-chip quantifies white thrombus formation and the PL-chip quantifies platelet thrombus formation. We assessed the antithrombotic abilities of various non-vitamin K antagonist oral anticoagulants (NOACs) using T-TAS. One hundred and three consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The T-TAS ® was initially developed to monitor the efficacy of anticoagulants [10]. Using the T-TAS ® , we recently demonstrated that blood samples from patients who had taken NOACs showed less ex vivo fibrin-rich thrombus formation under a constant low rate flow condition [11]. This study supported the usefulness of the T-TAS ® for monitoring the anticoagulant effects of NOACs in clinical practice.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…The T-TAS ® was initially developed to monitor the efficacy of anticoagulants [10]. Using the T-TAS ® , we recently demonstrated that blood samples from patients who had taken NOACs showed less ex vivo fibrin-rich thrombus formation under a constant low rate flow condition [11]. This study supported the usefulness of the T-TAS ® for monitoring the anticoagulant effects of NOACs in clinical practice.…”
Section: Introductionmentioning
confidence: 57%
“…Although the rivaroxaban group had less athero-thrombogenicity at the trough in the AR-chip analysis, this group had a similar capacity for platelet thrombus formation at any time point in PL-chip analysis, as compared to the apixaban group. We previously reported that blood samples from patients who were taking NOACs, including dabigatran, rivaroxaban and apixaban, had significantly lower PL-AUC levels at trough than control blood from patients who were not receiving any anticoagulant [11]. Taken together, PL analysis by T-TAS ® for patients was influenced by NOACs administration, but it was not suitable for the quantitative assessment of platelet function of NOACs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies investigated the effects of anti-platelet or anti-coagulant drugs on T-TAS measurements [41, 42]. One study that evaluated the effects of warfarin or direct-acting oral coagulants (DOACs) with T-TAS [43] showed a decrease in AR-AUC30, similar to the results of STUDY 1.…”
Section: Discussionmentioning
confidence: 73%
“…The topic of anticoagulants was dealt with by Idemoto et al [10] in which scientists assessed the effect of antithrombotic abilities of various novel oral anticoagulants (NOACs) using T-TAS as a useful tool for monitoring antithrombotic effects using both types of chips, and performed common coagulation tests. Authors evaluated the area under the flow pressure curve to quantify antithrombotic ability using T-TAS.…”
Section: Assessment Of Platelet Functionmentioning
confidence: 99%